Surfaces and Interfaces for Renewable Energy - Fernández-García, Aránzazu; Manzano Agugliaro, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Environmental problems derived from the massive use of conventional energy resources are one of the main issues that our society has been facing in recent decades. Renewable energies (and particularly solar energy) have become a highly competitive means to meet the world’s increasing energy demands in a sustainable and clean manner. One of the key research challenges for the commercial deployment of several solar energy technologies is focused on the development of feasible and durable coatings that withstand appropriate optical and thermal performance over the lifetime of the solar facilities. This book addresses a number of relevant aspects related to coatings for renewable energies, including a deep survey of coatings used in photovoltaic solar energy, the development of a superhydrophobic and thermal stable silica coating that is potentially suitable for various industrial applications related to renewable technologies, the development of coatings to improve the resistance of structural materials used in concentrating solar thermal technologies with molten salts, and several research works related to solar reflectors for concentrating solar thermal technologies (such us the advanced analysis of the corrosion, the suitability of anti-soiling coatings, and the development of top protective coatings for high-temperature secondary concentrators).